Pengaruh Logo Therapy Terhadap Kecemasan Penderita Kanker Di Rumah Singgah Kota Bengkulu - Muhammad Fachri; Mardiani Mardiani; Septiyanti Septiyanti; Hendri Heriyanto; Sahran Sahran (Tribhuwana Tunggadewi University, 2026)
As a chronic condition, cancer frequently triggers psychological distress, with patients often experiencing anxiety, impaired concentration, guilt, pessimism, deep sadness, and sleep disturbances. These psychological symptoms not only exacerbate physical decline but also severely diminish overall quality of life. Cancer complications include metastasis to other organs, side effects of therapy such as nausea and fatigue, weakened immunity, nutritional disorders, psychological issues, chronic fatigue, and blood abnormalities such as anemia and clotting disorders. Logo therapy serves as an intervention focused on helping individuals find existential meaning, thereby alleviating anxiety. The purpose of this study is to determine whether there is an effect of Logo therapy on the anxiety of cancer patients at Rumah Singgah, Bengkulu city. Utilizing a pre-experimental design involving a total sample of 35 participants. The sampling technique used was non-probability with purposive sampling, anxiety was measured via the Visual Analogue Scale – Anxiety (VAS-A). Statistical analysis using paired t-test yielded a p-value of 0.001 ? 0.05, demonstrating that Logotherapy significantly reduces anxiety in cancer patients